Right to effective judicial protection and right to enforcement of final judgments in Law n.° 29497, New Labor Procedure Law - Espinoza Montoya, Cecilia Leonor (2023)
The right to effective judicial protection will be studied to show that the actual, timely and in its own terms execution of judicial decisions with the quality of res judicata, constitutes part of its essential content; and, being the obligation of every judge the materialization of the same, it is necessary to verify if the provisions contained in Law No. 29497, the New Labor Procedure Law (NLPT), fulfill this purpose, favoring its realization within a reasonable time or if, on the contrary, this stage of execution constitutes the bottleneck of the new Peruvian labor procedural model, violating the effectiveness of what has been decided; in a process, whose pre-eminence of orality and immediacy, has contributed profoundly to the satisfaction of the right of action of workers and employers, with the effective and prompt declaration or denial of their claimed rights.